Stereotyp Słoweńca „ofiary” w przekładzie powieści Vlada Žabota Wilcze noce - Gruda, Marlena (Przekłady Literatur Słowiańskich, 2013)
Stereotypical Slovene victims novels in translation using Vlado Žabot’s novel Wilcze noce The novel Wilcze noce of Vlado Žabot is the source of knowledge about the Slovene character and stereotype including heterosterotype, formed under the influence of the cultural diversity of Slovenia, its historical and socio-political events. This unevenness of character is plain in the language of translation, in the semiotic and semantic structure. The polish reader can because of the translation of the novel Wilcze noce, come to know the stereotypical of Slovene as a person with strong self-destructive tendencies realized by the means of the ritual suffering at the same time influencing the ‘Other’ in the form of daily life rituals, group violence and self-sacrifice. The text of the translation was shaped 14 years after the first original Slovene edition and is a form of coming to terms with a change of the image of the Slovene in Polish and Slovene mentality. Key words: victim, Slo venian, self‑sacrifice,passivity, pain, space